Math, asked by Anonymous, 1 year ago

Find out the following

Attachments:

Answers

Answered by sumu27
3
Hope it helps you :)
Attachments:

Anonymous: thanks
sumu27: Welcome :)
Answered by Prakhar2908
2

Given,


x - y = 2√3 and


xy = 1


To find,


x+y


Main solution :


(x-y)^2 = x^2 +y^2 -2xy


Substituting the values that we know :-


(2√3)^2 = x^2+y^2 -(2×1)


12 = x^2 + y^2 -2


x^2 + y^2 = 12 + 2


x^2 + y^2 = 14


Now,


(x+y)^2 = x^2 + y^2 + 2xy


Substituting the values that we know :-


(x+y)^2 = 14 + (2×1)


(x+y)^2 = 14 + 2


(x+y)^2 = 16


(x+y) = √16


(x+y) ± 4



Answer :- The value of (x+y) is ± 4.





Similar questions
Physics, 1 year ago